2015
DOI: 10.1186/s12885-015-1370-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of lymphovascular invasion in patients with resectable gastric cancer: a large retrospective study from Southern China

Abstract: BackgroundThe focus of this study was to assess the impact of lymphovascular invasion (LVI) on both the recurrence of cancer and the long-term survival of Chinese patients with resectable gastric cancer (GC).MethodsA retrospective analysis of the clinicopathological data for 1148 GC patients who had undergone gastrectomy with regional lymphadenectomy was performed. The primary objective was to assess the correlation between LVI and post-surgery outcomes for each patient. This was done by routine H & E staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 33 publications
5
38
0
Order By: Relevance
“…Our study found a significant correlation between LNR and lymphovascular invasion and perineural invasion. Deng et al and Li et al have in their study concluded that LVI and PNI are independent prognostic factors in gastric carcinoma [9,10]. In the current study, LVI (p<0.05) and PNI (p<0.05) were found to have a significant statistical correlation with LNR.…”
Section: Discussionsupporting
confidence: 60%
“…Our study found a significant correlation between LNR and lymphovascular invasion and perineural invasion. Deng et al and Li et al have in their study concluded that LVI and PNI are independent prognostic factors in gastric carcinoma [9,10]. In the current study, LVI (p<0.05) and PNI (p<0.05) were found to have a significant statistical correlation with LNR.…”
Section: Discussionsupporting
confidence: 60%
“…Many previous studies have reported that LI, VI and PNI are adverse prognostic factors in other cancers, such as in colorectal, 17 gynaecological, 18 breast 19 and pancreatic 20 cancers. In gastric cancer, LI, 21 VI 22 and PNI 23 have all been reported as adverse prognostic factors, although this is predominately in patients who have not received neoadjuvant therapy. Jhawer et al 24 reported that perineural invasion was associated with worse outcomes in a study of 38 post-neoadjuvant patients, and Zhu et al 25 reported LI and PNI (but not VI) data for 192 post-neoadjuvant patients, showing worse survival if one factor was present, but with no assessment of the additive risk of multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the number of removed and involved LNs and the resulting pN-category and LNR, biological factors like lymphovascular invasion are of prognostic relevance. Several studies have shown the negative prognostic impact of lymphangiosis in all resected gastric cancer patients (30,31) or even in pN0 (32,33) and suggested adjuvant therapies in this subgroup of patients (30,32).…”
Section: Prognostic Role In Primarily Resected Gastric Cancermentioning
confidence: 99%